Patient Identification Impact Towards Patient Safety - Laurensia Brigitta Astinawati; Ratna Indrawati; Rokiah Kusumapradja; Endang Ruswanti (Journal of Multidisciplinary Academic, 2021)
The big issue that was happened in X Hospital particularly in 2018 is mainly related to the patient’s status assessment and effective communication. It focuses on reporting critical laboratory value which can inhibit the follow-up of treatment and patient safety. This research aims to provide empirical evidence of patient identification effect and effective communication of patient safety through the quality of hospital services. A quantitative analytical method with a causality research design was used as the research method. The analysis unit is the inpatient unit in X hospital. In this study, the multinomial logistic analysis and multiple regression were used for data analysis. The results of this research showed that the patient’s identification and effective communication as well as the quality of hospital services were significantly affected to patient safety. In this study, we obtain the patient identification has positively affected and significant on patient safety and quality of hospital services. For the effective communication, which focuses on reporting critical laboratory value, does not affected patient safety and quality of hospital services. Quality of hospital services does not mediate patient safety cause patient’s identification, and effective communication influence directly on patient safety.